Analysis of technologies of forming details from sheet thermally strengthened aluminum alloys - Романов, Богдан Сергійович; Кагляк, Олексій Дмитрович; Лутай, Анатолій Миколайович; Головко, Леонід Федорович (Technology audit and production reserves, 2015)
This article is devoted to study ways of forming thermally-hardened alloys, including aluminum and titanium. The authors analyze the advantages and disadvantages of traditional methods of forming such as bending to free press, rolling on three and four roll bending machines, blast forming, bending with stretching on special robots or pulling presses and combined processing methods. These methods require special technological equipment and highly skilled performers; require performance processing for a large number of transactions and conversions and is labor-intensive; after the formation it is necessary to carry out additional processing to reduce surface roughness. These processes are not quickly adjustable that in a single and small batch production of double curvature surfaces resulting in increased cost of the final product. The authors proposed to use for the manufacture of parts, from the above materials, laser forming process that is flexible, quickly adjustable and has enough performance. In addition, the authors suggest using forced cooling of the sample during processing that will increase the productivity of the process and additionally prevent thermal softening of the material. The use of laser forming for forming thermally-hardened aircraft materials will simplify and reduce the cost of the process of manufacturing parts of double curvature without loss of performance.